Effects of Trichinella spiralis excretory-secretory antigens on expression of indoleamine 2, 3-dioxygenase on dendritic cells in vitro - Yu Wenhao; Yuan Xuhong; Zhai Peng; Li Xiaoyun; Han Caixia (Parasite)
Indoleamine 2, 3-dioxygenase (IDO) is a potent immunoenzyme found in dendritic cells (DCs). Research has demonstrated that Trichinella spiralis induces IDO expression in the host immune response through its excretory-secretory (ES) antigens. However, the role of IDO in the immune response to T. spiralis remains unclear. To examine the effects of T. spiralis ES antigens on IDO expression in DCs in vitro, assessments were conducted using qRT-PCR, Western blotting (WB), flow cytometry, and siRNA transfer. The findings indicated that ES antigen stimulation upregulated IDO expression in DCs in vitro. Furthermore, ES antigen significantly enhanced the expression of the proinflammatory cytokines TNF-α and IFN-γ, along with the anti-inflammatory cytokine IL-10, downstream of IDO in DCs. Flow cytometry analysis confirmed that surface molecules CD40, MHC-II, CD80, and CD86 on DCs were upregulated following stimulation with ES antigen and lipopolysaccharide (LPS). Compared to the ES antigen alone, siRNA620 effectively inhibited IDO levels, demonstrating a statistically significant reduction. Continuous stimulation of DCs by ES antigens may lead to immune tolerance through the activation of IDO-mediated inflammation-associated factors. These results suggest that IDO expression in DCs plays a crucial role in T. spiralis infection.